Integration of Fluorescent Functionality into Pressure-Amplifying Metal-Organic Frameworks - Walenszus, Francesco; Evans, Jack D.; Bon, Volodyrnyr; Schwotzer, Friedrich; Senkovska, Irena; Kaskel, Stefan (Chemistry of Materials, 2021)
The flexibility of soft porous crystals, i.e., their ability to respond to external stimuli with structural changes, is one of the most fascinating features of metal-organic frameworks (MOFs). In addition to breathing and swelling phenomena of flexible MOFs, negative gas adsorption (NGA) and pressure amplification (PA) are the more recent discoveries in this field initially observed in the cubic DUT-49 framework. In recent years, the structural contraction was monitored by physisorption, X-ray diffraction, nuclear magnetic resonance (NMR), and electron paramagnetic resonance (EPR) techniques, providing only limited information about the electronic structure of the ligand. In this work, we designed a new ligand with a fluorescent core in the linker backbone and synthesized three new MOFs, isoreticular to DUT-49, denoted as DUT-140(M) (M-Cu, Co, Zn), crystallizing in the space group Fm3¯ m. DUT-140(Cu) can be desolvated and is highly porous with an accessible apparent surface area of 4870 m2 g-1 and a pore volume of 2.59 cm3 g-1. Furthermore, it shows flexibility and NGA upon adsorption of subcritical gases. DUT-140(Zn), synthesized using postsynthetic metal exchange, could only be studied with guests in the pores. In addition to the investigation of the adsorption behavior of DUT-140(Cu), spectroscopic and computational methods were used to study the light absorption properties.
CRIS-Team Scopus Importer:2022-04-14